2018
DOI: 10.1007/s00221-018-5374-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of action–outcome contingency on motivation from control

Abstract: The sense of agency is defined as one's sense of control over one's actions and their consequences. A recent theory, the control-based response selection framework (Karsh and Eitam, Motivation from control: a response selection framework. The sense of agency, Oxford University Press, New York, 2015a), suggests that actions associated with a high sense of agency are intrinsically rewarding and thus motivate response selection. Previous studies support this theory by demonstrating that factors impacting on sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Article the contingency between one's action and sensory feedback) has a reinforcement effect on the frequency of behavior (Rochat and Morgan, 1995;Rovee and Rovee, 1969). Furthermore, Karsh and Eitam suggested that control is an internal reward for humans, enhancing the speed of action execution and increasing the frequency of action selection (Karsh and Eitam, 2015;Karsh et al, 2016;Penton et al, 2018). We also observed this phenomenon in the moving distance among different conditions of control context (Figure 6A, see below for details of statistics).…”
Section: Kinematic Analyses: Timeline Of Control Sensingsupporting
confidence: 57%
“…Article the contingency between one's action and sensory feedback) has a reinforcement effect on the frequency of behavior (Rochat and Morgan, 1995;Rovee and Rovee, 1969). Furthermore, Karsh and Eitam suggested that control is an internal reward for humans, enhancing the speed of action execution and increasing the frequency of action selection (Karsh and Eitam, 2015;Karsh et al, 2016;Penton et al, 2018). We also observed this phenomenon in the moving distance among different conditions of control context (Figure 6A, see below for details of statistics).…”
Section: Kinematic Analyses: Timeline Of Control Sensingsupporting
confidence: 57%
“…The main dependent variables were the median RT and correct response rate for each block. The median is robust to outliner data (Whelan 2008 ), and therefore, a previous study analyzed medians instead of means of RTs (Penton et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The temporal dynamics in each experiment were also considered to confirm the immediate facilitation of each action effect. As a factor in control feedback, previous studies typically manipulated the contingency (Eitam et al 2013a ; Karsh and Eitam 2015a ; Karsh et al 2016 ; Penton et al 2018 ) or temporal contiguity (Eitam et al 2013a ; Karsh and Eitam 2015a ; Karsh et al 2016 ) between action and effect. Compared to the contingency, the contiguity appeared less likely to affect explicit knowledge of the degree of control (Karsh et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study aims to overcome these limitations by using the recently discovered motivation from control (Eitam et al, 2013; Hemed et al, 2019; Karsh & Eitam, 2015a; Karsh et al, 2016; Penton et al, 2018) to explore whether and how the effectiveness of an action is modulated in a dynamic environment.…”
Section: The Dynamic Evaluation Of a Motor Program’s Effectivenessmentioning
confidence: 99%